Pemberdayaan Kelompok Pelaku Usaha Handycraft di Desa Bibis Kasihan Melalui Pelatihan Digital Marketing - Wijayanti, Palupi Sri; Herawati, Tri Ratna; Warniasih, Kristina; Yuwono, Ahmad Agung (Universitas Nusantara PGRI Kediri, 2023)
This community service aims to provide assistance for handicraft business actors in Bibis Kasihan Bantul Village regarding the concept of digital marketing and empower these business actors to have various promotional videos. The community service activities are carried out through seven stages: site analysis, problem identification, determination of work goals, problem-solving design, social approach, implementation of service activities, evaluation of activities, and results of service. In the last stage, the closing is done by providing an evaluation of the video marketing that has been owned by business actors by looking at the digital footprint of followers and viewers. The results of the service showed an increase in posting business products through social media. In addition, this service is expected to have an impact on the community to optimize sales through digital marketing.